Water pH Measurement Instrument for Aquaculture using Titration Methods - Kurnia Illahi; Fajar Mukharom Darozat (Research on Instrumentation, 2024)
Indonesian aquaculture is one of the activities supporting production and economic activities in the fisheries sector locally and nationally. The endurance of the fish body is very dependent on the quality of the water used. One of the water quality parameters is the degree of acidity (pH). The problem in measuring the pH of water is the limited use of the pH meter sensor because the sensor probe must be cleaned regularly. One solution to overcome this problem is to make a water pH measuring instrument for aquaculture using the titration method. This tool is designed to make it easier for aquaculture farmers to measure the pH quality of water without touching the fish pond water. Research was conducted to determine the tool's design and performance specifications. The performance specifications of the water pH measuring instrument consist of mechanical design and electronic design. The results of the color reading of the pH value of the device can be displayed on a serial monitor through the Arduino IDE application or the Bluetooth terminal serial application on Android. The design specifications of the water pH measuring instrument consist of the accuracy and accuracy of the measurement of the pH value of water with the following details: The average pH value reading error is 1.027% with an average accuracy of 98.973% and an average accuracy of 99.419%.